Equality for whom? - Jalušič, Vlasta (Teorija in praksa, 2020)
Based on original fieldwork research (analysis of legislation, interviews with candidates and gatekeepers, and focus groups), the article identifies some of the less visible obstacles to women's participation in local politics in Slovenia. Between 2014 and 2018, 35.6% of parliamentary representatives were women while the share of women ministers in the Slovenian government was 50%. Considerably fewer women were involved in politics on the local level, with just 7.6% holding the position of mayor in the same period and 10 municipal councils were without any women at all. This article discusses the reasons for such subnational variations in women's representation in local politics. The analysis leads to the main conclusion that to change the low representation in certain local councils it is necessary to introduce a well-designed reform of the electoral system and measures related to gender mainstreaming, family life, and partnership roles.
Keywords: delež žensk; enakost spolov; Gender inequality; Local authority; Lokalna oblast; lokalna uprava; Spolna neenakost; Women; Women and democracy; Ženske; Ženske in demokracija